The Depiction of Gender Roles in a Singaporean Parenting Magazine - Nhi, Lê Phước Thục (VNU Journal of Foreign Studies; Vol 31 No 4, 2015)
This paper reports the analysis of 22 pictures and 5 full text articles from the Singaporean parenting e-magazine, The New Age Parents [1] to examine how gender roles of both parents and children in Singapore are depicted. Especially, such aspects as colours, clothing, toys, accessories, postures in the pictures and linguistic usage in the texts are scrutinised. The findings indicate that in all images, the fathers have a proclivity to stand more in the foreground or in a protective stance. In contrast, these pictures present mothers holding their babies tenderly, positioned on the inside, which denotes “the weaker sex” of mothers. The images also show that pink and light colours are associated with girls and mothers, while blue, primary and bold colours are connected with boys and fathers. In addition, the articles describe the parenting roles of mothers more than those of fathers. Even when fathers’ roles are discussed, they are referred to or compared to those of the mothers. None of the articles advocates any change in the mothers’ roles, whereas, it is recommended that paternal roles should be slightly modified to be tenderer and include certain tasks for fathers that used to be associated with only mothers. Keywords: Singapore, gender roles, parenting.